CEPHALOMETRIC SASSOUNI PLUS ANALYSIS USAGE FOR EVALUATING THE EFFECTIVENSS OF DISTAL BITE TREATMENT WITH AN ORTHODONTIC APPLIANCE WITH A MOVALE RAMP - P.S. Flis; V.V. Filonenko; N.M. Doroshenko (Ukrainian Medical Stomatological Academy, 2017)
Introduction. The effectiveness assessment of the removable orthodontic appliance with a movable ramp in the treatment of distal bite in a mixed occlusion period was carried out by cephalometry. Materials and methods. For the cephalometrical analysis of patients with distal bite in a mixed occlusion period of main and comparison groups Sassouni plus method was used. This method has certain anatomical landmarks and includes investigation of linear, angular and radius parameters with a high level of results individualization. The main group (9 patients) was with the new removable orthodontic appliance, which includes a plastic base on the upper jaw, vestibular arc, retaining clasps and movable ramp. The basis of the appliance and ramp are connected by the two club-shaped springs (torsion springs). They allow us to provide a prolonged contact with the ramp and lingual surfaces of the lower frontal teeth at rest and reduce the rigidity of the appliance. Comparison group (7 patients) was treated with the Schwarz' appliance with a ramp. Duration of treatment was approximately 10-12 months. The data of cephalometric analysis was hold by a number of parameters that were most informative in the study. Next parameters was evaluated: Skeletal A-P, Skeletal Vertical, Upper Incisor, Upper Incisor to PP, Lower Incisor, Effective Length of Premaxilla, Maxilla Position, Maxilla body size, Mandible Position, Mandible body size, Gonial Angle, NSAr angle (Saddle angle), H angle, Upper Lip angle. Results. Analysis was made before and after treatment. The data table with investigation results was made to see clean picture of anatomical structures changes. Superimposition of cephalometric images before and after treatment with the structural landmarks of skull base (supraorbital plane Cl-RO and Si) was made. Cephalometrical study results showed that most of patients (75.0%) had a skeletal distal tendency as point B was placed behind the A arc by -2,22 ± 0,04 mm in the main group and -2,76 ± 0,04 mm in the comparison group. After treatment skeletal sagittal ratio was improved in both groups. The angle of the upper incisors decreased by 0,78 ± 0,36° in the main group and by 1,02 ± 0,04° in the comparison group. In patients with protrusion of the angle of the upper incisors decreased by 3,08 ± 0,12° in the main group and by 2,81 ± 0,05° in the comparison group. The angle of the lower incisors slightly increased in the main group by 0,56 ± 0,04° and in the comparison group by 1,02 ± 0,06°. Despite the fact that the ramp of the appliance influences the position of the lower jaw in general and promotes its movement forward while masticatory muscles action, but in place of appliance's force vector application, still the forward tipping effect of lower incisors is observed. It should be noted that in the main group this effect was slightly lower. This, in our opinion, may be associated with reduced stiffness of the new appliance. After the treatment Mandible Position parameter increased by 2,26 ± 0,06 mm in the main group and by 3,11 ± 0,17 mm in the comparison group. Conclusions. The removable orthodontic appliance with a movable inclined plane allows us to improve the over jet ratio on the dental alveolar level by changing the torque of the upper frontal teeth and allows to move forward the lower jaw. The stability and degree of this displacement depends on the duration of treatment and the patient's ability to follow recommended time of usage. Reducing the stiffness of the appliance by springs had a positive effect on the lower incisors torque control during the treatment.